Interaction of metallothionein and ß2-microglobulin and its effect on ß2m fibrillogenesis - Quiming, Noel Samson 1976- (c2005.)
"Fluorescence spectroscopy and Far-UV circular dichroism (CD) were used to study the interaction of ß2-microglobulin and metallothionen (MT). All spectroscopic techniques gave proofs on the interaction of ß2m and MT. At pH 4.0, 7.0 and 9.0 quenching of ß2m fluorescence in the presence of MT were observed suggesting the possibility of binding of the two proteins. Fluorescence quenching experiments were also performed using acrylamide and KI as quenchers. Quenching of ß2m in the presence of MT gave nonlinear Stern-Volmer plots showing a static quenching mechanism. In addition, the larger quenching constants when MT was present indicated that the interaction of the two proteins resulted in the exposure of the tryptophan residues of ß2m. Far-UV CD revealed that the interaction between ß2m and MT resulted in an increase in ß2m structure and a decrease in the random coil structure of ß2m indicating that the interaction of the two proteins caused ß2m to assume a more ordered secondary structure. Kinetic studies on ß2m fibrillogenesis showed that the rate of fibril formation is slower in the presence of MT signifying that the more ordered structure of ß2m as a result of its binding interaction with MT may prevent fibril formation. This is consistent with the fact that a partially unfolded structure of ß2m is necessary for fibrillogenesis. Binding constant and number of binding sites were determined from the quenching data and were found to be 2.452 uM and 0.91, respectively."
"April 2005."
Vita.
Thesis (M.S. Chemistry)--University of the Philippines, Diliman.
Keywords: Metallothionein; Fluorescence spectroscopy; Chemistry; Chemical kinetics